Food intolerance and allergy in the metropolitan region of Belém – PA (Research, Society and Development, 2022)
The purpose of this article is to show a mountain of people who are allergic and intolerant. Reactive foods that cause allergies in the Belém metropolitan area during the 2020-2022 period. The research was conducted through a cross-sectional study for G-Suite's online electronic form for social media education and propagation. All participants are over the age of 18 and have signed the Free and Informed Consent Form (ECIF). It interviewed 390 people from Belém. They are female, brownish in colour, simple, and with an elevated formation. The prevalence food to 180 people is lactose, shrimp, milk, shellfish, seafood, pork, eggs, artificial colors, gluten, pineapple, fish, cocoa, peanuts, preservatives, crab, coconut, orange, tree nuts, chocolate, melon, almonds, passion fruit, popcorn, pupunha, artificial condiments, English sauce, shoyu, ketchup, mayonnaise, sardines, other canned food, watermelon, banana, cheese, sprinkles, cupuaçu, guava.  So the research has been important, on the other hand, it is now needed for people who have not been surveyed at more databases.